2005
DOI: 10.1111/j.1600-0609.2005.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Repp86: a new prognostic marker in mantle cell lymphoma

Abstract: Based on these findings, repp86 expression is a new important prognostic factor in MCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…These data are in line with our results of repp86 in a large series of 94 patients with MCL (Schrader et al, 2005). Repp86 is a spindle apparatusassociated protein expressed only during S/G2/M, absent in G1 and G0, and thus displaying the same cell cycle expression pattern like geminin (Heidebrecht et al, 1997(Heidebrecht et al, , 2003Lygerou and Nurse, 2000;Wohlschlegel et al, 2000;Madine and Laskey, 2001;Hodgson et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These data are in line with our results of repp86 in a large series of 94 patients with MCL (Schrader et al, 2005). Repp86 is a spindle apparatusassociated protein expressed only during S/G2/M, absent in G1 and G0, and thus displaying the same cell cycle expression pattern like geminin (Heidebrecht et al, 1997(Heidebrecht et al, , 2003Lygerou and Nurse, 2000;Wohlschlegel et al, 2000;Madine and Laskey, 2001;Hodgson et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…As this cell cycle arrest has been shown by others Eward et al, 2004;Obermann et al, 2005;Tachibana et al, 2005), we could demonstrate that this has a clinical relevance in patients with MCLs. Our data on expression of repp86 in MCL (Schrader et al, 2005) showed that real proliferation activity is an important prognostic factor in MCL. On the other hand, patients with cell arrest (G1 arrest) indicated by high MCM6 expression also predict survival in this disease.…”
Section: Discussionmentioning
confidence: 61%
“…Actually, based on the recent European MCL Network's clinicopathological study of 304 cases of MCLs, the cell proliferation was identified as a strong prognosticator [7]. In addition, multivariate analyses exposed the immunohistochemically assessed Ki-67, topoisomerase IIα, and TPX2 level as the most effective prognostic factor in MCL patients, even superior to the International Prognostic Index and other clinical and histomorphological characteristics [6,14,15]. The predictive role of KI-67 was also confirmed for MCL patients treated with anti-CD20 therapy, and it was reported as an important biological marker also in addition to MCL International Prognostic Index [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The predictive role of various clinical and laboratory parameters in the MCL progression is conflicting [6][7][8][9][10][11][12][13][14][15]. Actually, based on the recent European MCL Network's clinicopathological study of 304 cases of MCLs, the cell proliferation was identified as a strong prognosticator [7].…”
Section: Introductionmentioning
confidence: 99%
“…45,46). Proliferation markers studied in MCL include Ki-67, topoisomerase IIa, MDM2, repp86, and survivin (47)(48)(49)(50)(51). However, except for Ki-67, none of these biomarkers have to date been validated in larger cohorts (Table 1).…”
Section: Ki-67 Index and Other Immunohistochemically Assessed Prolifementioning
confidence: 99%